Validation of the innovation capability construct using confirmatory factor analysis in Ecuador (2018)
The purpose of the article is to validate with employees of Ecuador, a scale of innovation capability. The study was conducted in two universities in Guayaquil, Ecuador with a sample of 610 postgraduate students working in various companies in the economic sector. Through the exploratory and confirmatory factor analysis, the reliability and validity of the scale was demonstrated. One of the main findings is that the scale, despite having been developed to measure innovation capacity in service companies, can be used in companies in Ecuador, regardless of the economic sector. In addition, technology is one of the dimensions that contribute the most towards innovation capability. © 2018.